Industri Pariwisata Halal: Pendorong Inovasi Untuk Halalpreneurs - Imam Azizuddin; Muhammad Hamdan 'Ainulyaqin (Jurnal Ilmiah Ekonomi Islam, 2022)
This paper describes halal tourism with various practices that have been carried out in the halal industry. This halal industry practice can provide opportunities for halal entrepreneurship in a reciprocal relationship with halal tourism. Presents halal tourism literature to define halal travel and provides an overview of opportunities for developing halal entrepreneurs to innovate halal products to provide more competitive results according to Sharia. This paper also provides new prospects for Halal Entrepreneurs that can enable them to start new businesses in the Halal tourism industry. This study contributes theoretically and practically in halal tourism and halal entrepreneurship. These findings can provide assistance to tourism actors, Halal entrepreneurs to promote Halal tourism products and services to meet the needs of Muslim tourists.